The Studies on pesticide properties from indigenous medicinal plants; antibacterial activity on plant pathogenic bacteria, Pseudomonas.syringae - Davaasambuu, Undarmaa; Davaadorj, Narantsatsralt (Mongolian Journal of Agricultural Sciences, 2021)
We tested the extracts from plants growing in Mongolia, such as Chelidonium majus, Artemisia annua L, and Hyoscyamus niger L, against bacterial angular spot plant disease, which is the most common and harmful in the greenhouses of Mongolia to determine a bactericidal activity of these plants in vitro on plant pathogenic bacteria, Pseudomonas.syringae The extracts of selected plants were used at 0.3, 0.6, 1.2, 2.5, 5.0, 10.0,15.0 mg/ml concentrates against plant pathogenic P.syringae bacteria, among them 0.3, 0.6 mg/ml concentrates did not show the zones of growth inhibition (ZGI). The zones of growth inhibition were observed at 1.2 mg/ml; it considered as minimum inhibition concentrate (MIC). The extract of Chelidonium majus, at MIC 1.2 mg/ml concentrate, the zones of growth inhibition 9±0.58mm, at 15 mg/ml concentrate 18.6±0.33mm; the extract of Artemisia annua L, at MIC 1.2 mg/ml concentrate, 7.3±0.33 mm, at 15 mg/ml concentrate 17.6±0.33mm, and the extract of Hyoscyamus niger L, at MIC 1.2 mg/ml concentrate, 7.3±0.33 mm, at 15 mg/ml concentrate 17.6±0.33mm were observed respectively. Antibacterial activity of the extract of Chelidonium majus, 55.1-107.8%, the extract of Artemisia annua L 44.89-97.94%, and the extract of Hyoscyamus niger L 36.74-90.42% against plant pathogenic bacteria, P.syringae be compared to a positive control (Kanamycin) estimated. Among these plant extracts, the highest antibacterial activity found at 5-15 mg/ml concentrates of the extract of Chelidonium majus, which was over than standard solution (Kanamycin). Ургамлын пестицид шинж чанарын судалгаа; фитопатоген Pseudomonas.syringae бактерийн эсрэг идэвхиийг тодорхойлсон дүн Монгол орны уугууль эмт шинж чанар бүхий тарималжсан их шүүдэргэнэ(Chelidonium majus), байгалийн морин шарилж (Artemisia annua L), хар лантанз (Hyoscyamus niger L) зэрэг ургамлаас өтгөн ханд бэлтгэж, фитопатоген Pseudomonas.syringae бактерийн эсрэг туршиж, пестицид (бактерицид) шинж чанарыг судлав. Ургамлуудын хандыг 0.3, 0.6, 1.2, 2.5, 5.0, 10.0,15.0 мг/мл концентрацитайгаар тус тус авч фитопатоген P.syringae бактерийн эсрэг туршихад, 1.2 мг/мл концентрациас эхлэн мэдэгдэхүйц зоныг үүсгэсэн нь энэхүү бактерийн эсрэг идэвхитэй хамгийн бага концентраци болохыг тодорхойлов. Их шүүдэргэнэ ургамлын ханд нь хамгийн бага идэвхтэй 1.2 мг/мл концентрацидаа 9±0.58 мм, хамгийн их 15 мг/мл-дээ 18.6±0.33мм, Морин шарилж ургамлын ханд нь хамгийн бага идэвхтэй 1.2 мг/мл концентрацидаа 7.3±0.33 мм, хамгийн их 15 мг/мл-дээ 17.6±0.33мм, харин Хар лантанз ургамлын ханд нь хамгийн бага идэвхтэй 1.2 мг/мл концентрацидаа 7.3±0.33 мм, хамгийн их 15 мг/мл-дээ 17.6±0.33мм зоныг тус тус үүсгэсэнээс үзэхэд эдгээр ургамлуудын ханд нь энэхүү фитопатоген бактерийг дарангуйлах өндөр идэвхитэй байна. Их шүүдэргэнэ ургамлын ханд нь эерэг хяналттай харьцуулахад 55.1-107.8%, морин шарилжийн ханд 44.89-97.94% , хар лантанз ургамлын ханд нь 36.74-90.42% зэрэг бактерийн өнцгөн толбожилт өвчнийг үүсгэдэг P.syringae бактерийг эсрэг идэвхийг үзүүлснээс их шүүдэргэнэ ургамлын ханд нь дарангуйлах шинж чанарын хувьд эерэг хяналтаас давсан өндөр үр дүнг үзүүлэв. Түлхүүр үг: ургамлын ханд, пестицид (бактерицид) шинж чанар, in vitro, фитопатоген бактери